Neighborhood characteristics of expanded access patients at an academic referral center - Misty Gravelin; Jeanne Wright; Adrian Weyhing; Vikas Kotagal (Journal of Clinical and Translational Science)
Expanded access (EA) is a United States regulatory approach for the use of investigational drugs/devices that do not yet have conventional approval, in clinical care contexts. We conducted a retrospective study to analyze the neighborhood characteristics of patients who have received EA treatments at our academic medical center between 2018 and 2023. EA patient neighborhoods showed lower median family income, lower proportion of bachelor’s degree graduates, and a higher proportion of people identifying as non-Hispanic White ethnicity compared to the surrounding (Washtenaw) county. These differences may underly differential interest in EA treatments or may point to disparities in access to evidence-based care.